Crítica de libros. Korhonen, Senja y Sumuvuori, Johanna (eds.) (2006): From Conflicts to Development: An Introduction to EU Civilian Crisis Management, Jyväskylä, Committee of 100 in Finland / KATU - Ruiz, Xira (UNISCI Discussion Papers, 2007)
Sin resumen